Pengabdian Kepada Masyarakat (PKM) melalui Penyuluhan tentang Penyakit Kanker Prostat, Kanker Serviks, dan Kanker Payudara - Albert Hasibuan; Anita Sriwaty Pardede; I.Gusti Ngurah.Y.Usdayana; Halisa Kurniati; Fransiscus A.C.Wakumoan; Rachel Amanda Indaryati (LOSARI DIGITAL, 2026)
Kanker is one of the leading causes of death in Indonesia. The three most common types of Kanker are prostate Kanker, cervical Kanker, and breast Kanker. Lack of public knowledge about symptoms, prevention, and early detection is one factor in the increasing number of deaths from Kanker. The purpose of this Community Service is to increase insight into Kanker, raise awareness of the dangers of Kanker, and anticipate the possibility of developing Kanker early. The method used is counseling. The results of the pretest and posttest percentages showed that adult knowledge before the counseling was 71% and after the counseling was 98%. Therefore, it can be said that there was a 26% increase after the counseling. The results obtained are increased knowledge, insight, awareness, and early anticipation of Kanker. As a form of concern for the health of the congregation, it is necessary to carry out health counseling activities regarding prostate, cervical, and breast Kanker in the HKBP Church environment. The PKM activity is a collaboration between lecturers from STIKes PGI Cikini and the HKBP Pejuang Resort Palmarum Bekasi church, which synergizes in improving the health status of the community through promotive and preventive efforts.